Firm export market performance: the case in Uganda - Is’haq, Amandu Yassin; Haque, A. K. M. Ahasanul (World Business Institute, 2017)
Firm export performance is declining across industries and economies around the world. Despite numerous researches to explain the decline, there are controversies and lack of consensus as to what determines firm export performance. This paper was developed to identify and explain determinants of, and propose a firm export performance model from a developing economy perspective. A quantitative cross-sectional survey of 250 firm export executives from selected firms and industries was conducted. Psychometric analyses of descriptive statistics, reliability, exploratory, confirmatory, and validities were performed. Structural equation modelling was used to examine the hypothesised relationships and validate the proposed firm export performance model. The results identified export market orientation, market environment, organizational learning, market information system, export market strategy and organizational innovation capability as determinants of firm export performance. This implies that an export development strategy needs implementation and practice of these predictors. This would consequently enable the firm to gain competitiveness, achieve its strategic growth objectives and transform the national economy into a more desirable one.